Functional genomics of pollen tube–pistil interactions in Arabidopsis. (22nd March 2010) - Palanivelu, Ravishankar; Johnson, Mark A.
Abstract : The pollen tube represents an attractive model system for functional genomic analysis of the cell–cell interactions that mediate guided cellular growth. The pollen tube extends through pistil tissues and responds to guidance cues that direct the tube towards an ovule, where it releases sperm for fertilization. Pollen is readily isolated from anthers, where it is produced, and can be induced to produce a tube in vitro . Interestingly, pollen tube growth is significantly enhanced in pistils, and pollen tubes are rendered competent to respond to guidance cues after growth in a pistil. This potentiation of the pollen tube by the pistil suggested that pollen tubes alter their gene-expression programme in response to their environment. Recently, the transcriptomes of pollen tubes grown in vitro or through pistil tissues were determined. Significant changes in the transcriptome were found to accompany growth in vitro and through the pistil tissues. Reverse genetic analysis of pollen-tube-induced genes identified a new set of factors critical for pollen tube extension and navigation of the pistil environment. Recent advances reviewed in the present paper suggest that functional genomic analysis of pollen tubes has the potential to uncover the regulatory networks that shape the genetic architecture of the pollen tube as it responds to migratory cues produced by the pistil.